IMPACT OF PLANTING DATES ON THRIPS POPULATION AND TRANSMISSION OF GROUNDNUT BUD NECROSIS VIRUS IN EARLY POTATO - Bhatanagar, Anuj (Potato Journal, 2018)
ABSTRACT: The potato is grown in many parts of North-central and North-western parts of India as early cash crop fetching high remunerative price in the market. However, several species of insect pests infest this crop due to comparatively higher temperature. The most important among them is thrips (Thrips palmi Kerny). This pest can cause 20-60 % damage to early potato crop depending upon climatic conditions. With the increasing temperature due to global climate change, the incidence of thrips is expected to increase in central India. The yield losses by thrips are mainly due to transmission of groundnut bud necrosis virus (GBNV), resulting stem necrosis disease. Keeping the importance of this vector and transmission of viral disease, field experiment was carried out on dates of planting (15th September, 20th September, 25th September, 30th September, 5th October, 10th October) with the objective to collect the information on incidence of thrips and stem necrosis disease in relation to climatic factors during the years 2011, 2012 and 2013. The pooled data of three years revealed that highest thrips population (22.84/10 plant) was recorded in 15th September planted crop with (23.4%) incidence of stem necrosis disease. The high temperature (30-35 0C) and dry weather is favorable for the development of stem necrosis disease. There was low incidence of stem necrosis and thrips on crop during 2012 and 2013 as compared to 2011, due to no rains during September month. Pooled tuber yield data revealed that early planted crop was recorded low total tuber yield (10.79 t/ha) as compared to late planted crop (19.80 t/ha). Simple correlation studies revealed positive and significant correlation between incidence of thrips with stem necrosis disease, maximum temperature and minimum temperature while tuber yield showed significant negative correlation among the different dates of planting. Therefore, potato crop grown for table purpose will required better management tact ties right from planting.Â